2019
DOI: 10.1109/access.2019.2951926
|View full text |Cite
|
Sign up to set email alerts
|

Sina Weibo Bursty Event Detection Method

Abstract: In response to the recent frequent outbreaks of bursty events, if the supervision is not strengthened, the grievances caused by it will have an extremely negative impact on society. Therefore, how to effectively detect bursty events in social networks has become the focus of research. In order to eliminate the interference of local daily events generated by noisy data, this paper proposes a bursty event detection method for quantifying the influence of microblog text. Through the analysis of high-impact microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is also observed that the temporal relationships between terms are no featured; hence, event detection methods lose an important feature. There have been models that seek to overcome these problems [ 17 , 18 ]. In general, there have been issues of accuracy and efficiency in event detection [ 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…It is also observed that the temporal relationships between terms are no featured; hence, event detection methods lose an important feature. There have been models that seek to overcome these problems [ 17 , 18 ]. In general, there have been issues of accuracy and efficiency in event detection [ 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…Firms create social media accounts to post firm-generated content (FGC) for brand publicity. Visual content or images play a critical role in FGC because as the old saying goes, “a picture is worth a thousand words.” More than 120 million images are posted daily on Sina Weibo, a major microblogging platform in China, and 300 million images are uploaded to Facebook (Smith, 2013; Yang, 2019). Visual content has the ability to capture consumers’ attention, provoke emotional reactions, and increase ad persuasiveness, indicating its superiority over textual content in eliciting consumers’ emotions and recall (Bashirzadeh et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%